HYPOTHYROIDISM IN HEPATITIS C PATIENTS ON PEGYLATED INTERFERON THERAPY - Hameed, Muhammad Asim; Mehmood, Asif; Farooq, Muhammad Ahsan; Tayyab, Ghias un Nabi; Toor, Israr Ul Haq (Journal of Ayub Medical College Abbottabad, 2016)
Background: Chronic hepatitis has become a major health problem all over the world especially in the third world countries. The most common cause of chronic hepatitis in Pakistan is hepatitis C which can lead Toliver cirrhosis and hepatocellular carcinoma. In Pakistan Pegylated Interferon Alpha is still corner stone of therapy for chronic hepatitis C. One of the major side effect of this therapy is the development of thyroid dysfunction, i.e., hypothyroidism and hyperthyroidism. This study was done to assess the frequency of hypothyroidism in hepatitis C patients after three months of pegylated interferon therapy. Method: This study was conducted from 1st October 2013 to 31st march 2014 at outpatients department (OPD) of Gastroenterology and Hepatology, Lahore General Hospital Lahore. Descriptive case series study design was used. The sample of 200 patients was taken from the patients who visited OPD and fulfil the inclusion criteria of the study. Serum thyroid stimulating hormone level (TSH) was done before and after completion of three months therapy at centre for Nuclear Medicine (CENUM) laboratory, Mayo Hospital, Lahore by immune-radiometric assay (IRMA) and patients having TSH>4.0 mIU/L (normal range: 0.2-4.0 mIU/L) were considered hypothyroid. Results: The mean age of the patients was 36.29±8.5 years. One hundred and twenty-three (61.5%) were male and 77 (38.5%) were female. After 3 months of interferon therapy, 163 (81.5%) patients were euthyroid and 37(18.5%) patients were having thyroid dysfunction. There were total 29 (14.5%) hypothyroid patients; 8 (27.6%) were male and 21 (72.4%) female. Conclusion: It is concluded from this study that frequency of hypothyroidism in patients with chronic hepatitis C was 14.5% after treatment with pegylated interferon therapy for 3 months. Female patients were more prone to develop hypothyroidism as compared to male patients. Keywords: Hepatitis C Virus; hypothyroidism; pegylated interferon therapy